Cover Jurnal Fitopatologi Vol. 17 No. 1, Januari 2021 - Sri Hendrastuti Hidayat (Jurnal Fitopatologi Indonesia, 2021)
This editorial contains the front cover, editorial page and back cover of the Indonesian Journal of Phytopathology, Volume 17, No. 1, January 2021.